EDUKASI PENGGUNAAN MEDIA SOSIAL TIK TOK TERHADAP MINAT BELAJAR ANAK USIA DINI (4-5) TAHUN DI TK NURUL FATAH KALIBARU - Kunari Yusanti, Erika Dwi Afifah; Pascalian Hadi Pradana; Nurhafit Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of TikTok as a social media platform has become increasingly popular, even among young children. However, its impact on their learning interest remains unclear, raising concerns about its role in early childhood education—especially when used without parental supervision. This study aims to explore the influence of educational use of TikTok on the learning interest of early childhood students. The general objective is to understand how TikTok can be utilized as an educational tool that positively affects children’s interest in learning. The specific objective is to identify how educational content on TikTok influences children's motivation and interest in learning, as well as to examine the relationship between social media usage and early childhood learning engagement. This research employs a descriptive qualitative method, using in-depth interviews and observation as data collection instruments. The expected outcome is a comprehensive research report that describes the impact of educational TikTok use on children's learning interest and provides recommendations for parents, educators, researchers, and policymakers on how to enhance early childhood learning interest in the context of social media usage.